ANALISIS PENINGKATAN RUAS JALAN DESA TATENGGER KECAMATAN ANGKOLA MUARA TAIS KABUPATEN TAPANULI SELATAN - Alfiansyah Harahap; Julianto Lubis; Ferawati Artauli Hasibuan (STATIKA, 2026)
Roads are one of the most important land transportation infrastructures; therefore, a good pavement design is essential. In addition to connecting one place to another, a well-designed road pavement is also expected to provide safety and comfort for drivers, especially in supporting smooth traffic flow. The high growth of traffic resulting from economic development can create serious problems if it is not balanced with improvements in the quality of existing road facilities and infrastructure. Therefore, road conditions greatly affect the comfort and safety of every road user. The objective of this thesis is to identify the types of damage found on the Tatengger Village Road section in Angkola Muara Tais and to determine the appropriate maintenance treatment and the required thickness of flexible pavement for future road improvement or rehabilitation. The methods used in this research are the Indonesian Highway Capacity Manual Method and the component analysis method. Based on the results of the data analysis, it can be concluded that the types of damage found on the Tatengger Village Road section in Angkola Muara Tais include hairline cracks, potholes, patches, alligator cracks, waves, depressions, and longitudinal cracks, with a total damage percentage of 6.11%. The appropriate maintenance treatment is routine maintenance. Meanwhile, the required flexible pavement thickness for future improvement or rehabilitation consists of a 5 cm surface layer, a 20 cm base course layer, and a 10 cm subbase layer, with a planned service life of 20 years.